Predictive importance of the visceral adiposity index and atherogenic index of plasma of all-cause and cardiovascular disease mortality in middle-aged and elderly Lithuanian population - Tamosiunas, Abdonas; Luksiene, Dalia; Kranciukaite-Butylkiniene, Daina; Radisauskas, Ricardas; Sopagiene, Diana; Bobak, Martin (Frontiers in Public Health, 2023)
Background: Two indices: visceral adiposity index (VAI) and atherogenic index of plasma (AIP) during several recent years were implemented into epidemiological studies for predicting of cardiovascular diseases (CVD) and mortality risk. Our study aimed to evaluate the association of VAI and AIP with the risk of all-cause and CVD mortality among the Lithuanian urban population aged 45-72 years. Methods: In the baseline survey (2006 to 2008), 7115 men and women 45–72 years of age were examined within the framework of the international study Health, Alcohol and Psychosocial Factors in Eastern Europe (HAPIEE). 6671 participants (3663 women and 3008 men) were available for statistical analysis (after excluding 429 respondents with the missed information on study variables) and for them, VAI and AIP were calculated. The questionnaire evaluated lifestyle behaviours, including smoking and physical activity. All participants in the baseline survey were followed up for all-cause and CVD mortality events until 31st December 2020. Multivariable Cox regression models were applied for statistical data analysis. Results: After accounting for several potential confounders, higher levels of VAI (compared 5th quintile to 1st quintile) were associated with significantly higher CVD mortality in men (Hazards ratio (HR)=1.38) and all-cause mortality in women (HR=1.54) after 10-year follow-up. CVD mortality significantly increased in men with 0the highest AIP quintile compared with that for the lowest quintile (HR=1.40). In women, all-cause mortality was significantly higher for the 4th quintile of AIP as compared with the 1st quintile (HR =1.36). Conclusions: High-risk VAI levels were statistically significantly associated with all-cause mortality risk in men and women groups. The higher AIP level (5th quintile vs. 1st quintile – in men and 4th quintile vs 1st quintile – in women) was significantly associated with increased mortality from CVD in the men group and increased all-cause mortality in the women group.